Extremely high levels of thallium in the natural diet and drinking water of giraffes (Giraffa camelopardalis giraffa) - Jeaneme Kühn; Francois Deacon; Walter Purcell; Hendrik G. Visser; Marietjie Schutte-Smith (Environmental Advances, 2023)
The rapid expansion of the human population is causing significant harm to giraffe (Giraffa camelopardalis giraffa) populations. The growth of the industrial and urban sectors leads to the release of harmful substances into the environment. This surge in pollution stands as one of the primary threats to giraffes and their constrained habitats, contributing to the fact that two of the nine giraffe subspecies are listed as Critically Endangered on the IUCN Red List of Threatened Species.Using the optimised hotspot analyses from a previous study of the browsing patterns of GPS-tagged male and female giraffes at the Rooipoort Nature Reserve (RNR) the frequent areas (hot spots) where they feed, and drink water could be identified.The aim of the study was to identify whether there is any form of heavy metal contamination in the plants or water sources. The leaves of all the tree species at RNR were collected from the 20 locations that were frequented the most and analysed for heavy metals. Six metals were found in significant concentrations in the leaves, with the thallium concentration higher than the permissible range.Water samples from the Vaal River and water holes were also quantitatively analysed and the presence of aluminium, thallium, chromium, copper, iron, manganese, and zinc was confirmed.We have gained knowledge on the factors influencing giraffe health that can ultimately be used to guide management and legislative/policy decisions by private and public conservation managers suitable for the well-being and survival of giraffes when exposed to metals and/or low-quality diet. We conclude that the giraffes in RNR (and other animal species) are constrained in an environment that has toxic levels of thallium in their diet and water sources they cannot avoid. This would be the first study to investigate the effect of thallium on giraffe distribution and habitat use.